1994
DOI: 10.1104/pp.106.3.829
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Light-Harvesting Complexes (LHCs) of Photosystem II (Monomeric LHC IIb Complexes Are Intermediates in the Formation of Oligomeric LHC IIb Complexes)

Abstract: The light-induced assembly of light-harvesting complex (LHC) II PSI and PSII of higher plant thylakoid membranes include an evolutionarily conserved CC containing the photochemical reaction center and an LHC, the function of which is to absorb photons and to transfer excitation energy to the CC. The LHCs of both photosystems, LHC I and LHC 11, are composed of several distinct pigment-protein complexes. The proteins function to orient and space precisely their associated Chl and carotenoid molecules so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Two families of early light-inducible proteins (ELIPs) identified at 13-14 and 17-19 kDa by (32) are related to etioplast-to-chloroplast transformation (32,33). The major LHCII apoproteins are located between 25 and 28 kDa (34,35), and the fractional weight of the corresponding band rises Ϸ4.3-fold during greening ( Table 1). The assayed total protein͞lipid ratio was found to be 5 mg͞mg during greening and 6 mg͞mg for the mature green plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two families of early light-inducible proteins (ELIPs) identified at 13-14 and 17-19 kDa by (32) are related to etioplast-to-chloroplast transformation (32,33). The major LHCII apoproteins are located between 25 and 28 kDa (34,35), and the fractional weight of the corresponding band rises Ϸ4.3-fold during greening ( Table 1). The assayed total protein͞lipid ratio was found to be 5 mg͞mg during greening and 6 mg͞mg for the mature green plants.…”
Section: Resultsmentioning
confidence: 99%
“…The protein͞lipid mass ratio increases only during the maturation phase (Ϸ24-48 h) in which LHCII apoproteins dominate the SDS͞PAGE, in agreement with ref. 35. The growth of certain SDS͞PAGE bands, most notably LHCII, which binds most of Chl in mature thylakoids (9), and the 18:3 fatty acid content follow a time course similar to that of the Chl accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The Chl-or Zn-phe-complemented etioplast membranes in our experiments behave like thylakoid membranes at an early greening stage. In greening pea leaves, monomeric LHCII is accumulated 12-24 h prior to the appearance of trimeric complexes and then gradually disappears as the level of LHCII trimers increases (40). Consistently, when we inserted pLHCP into greening barley thylakoids at an early greening stage, without Chl or Zn-pheide added, the protease assay yielded LHCP-DP* exclusively, whereas insertions into thylakoids at later greening stages gave rise to gradually increasing amounts of trimeric LHCII as indicated by LHCP-DP.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Allen et al (1988) found that the inner antenna proteins ( 0 2 9 and CP24) of the CD3 wheat mutant in greening experiments were less affected than the peripheral trimeric LHCII*. This hierarchy corresponds to the well-documented order of appearance of these Chl-binding proteins during development: first the RC components of PSI and PSII, followed by the minor / inner antenna proteins of PSII (CP29,CP26, and CP24), and finally LHCI and peripheral (trimeric) LHCII (Dreyfuss and Thornber, 1994;Sigrist and Staehelin, 1994;Paulsen, 1995, and refs. therein).…”
Section: Control Thylakoid Morphologymentioning
confidence: 99%